A 2-center Comparative Study on Tonic Versus Burst Spinal Cord Stimulation: Amount of Responders and Amount of Pain Suppression. Issue 5 (May 2015) - De Ridder, Dirk; Lenders, Mathieu W.P.M.; De Vos, Cecile C.; Dijkstra-Scholten, Cindy; Wolters, Rian; Vancamp, Tim; Van Looy, Pieter; Van Havenbergh, Tony; Vanneste, Sven
Abstract : Introduction: Spinal cord stimulation is a safe and effective procedure applied for medically intractable neuropathic pain and failed back surgery syndrome. Recently, a novel stimulation paradigm was developed, called burst stimulation consisting of intermittent packets of closely spaced high-frequency stimuli. The design consists of 40 Hz burst mode with 5 spikes at 500 Hz per burst, with a pulse width of 1 ms and 1 ms interspike interval delivered in constant current mode. Methods and Materials: A retrospective analysis is performed looking at 102 patients from 2 neuromodulation centers, 1 in Belgium and 1 in the Netherlands. This consisted of 2 groups, 1 group who had become failures to tonic (conventional) stimulation and 1 group who still responded to tonic stimulation. All patients were switched from tonic to burst stimulation and the amount of responders as well as the amount of pain suppression was assessed. Results: Overall burst stimulation was significantly better than tonic stimulation and baseline. On average the pain on numeric rating scale (NRS) improved from 7.8 at baseline to 4.9 with tonic to 3.2 with burst stimulation. For the Belgian and Dutch centers combined, 62.5% of nonresponders to tonic stimulation did respond to burst stimulation, on average, with 43% pain suppression. Most responders to tonic further improved with burst stimulation; on average, pain suppression improved from 50.6% to 73.6.3%. The results (from both centers) did not differ for the amount of obtained pain suppression, only for the amount of responders, which could be related to the different profile of the 2 participating centers. Conclusions: Burst seems to be significantly better than tonic stimulation. It can rescue an important amount of nonresponders to tonic stimulation and can further improve pain suppression in responders to tonic stimulation.